1985
DOI: 10.1148/radiology.154.1.3880610
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral catheterization: mechanical versus manual control of bleeding.

Abstract: This study compared hand-held arterial compression with compression by a mechanical clamp to achieve hemostasis following transfemoral catheterization in 3,255 patients from six different hospitals. The time spent in manual compression of the artery averaged 33.5 minutes compared with 19.9 minutes using the clamp. The incidence of hematoma formation using the manual method was 6%; it was 2% using the mechanical device. No ischemic symptoms or complications resulted from the use of the holding device. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 0 publications
2
34
1
Order By: Relevance
“…With regard to the safety of the system, the results presented in this study clearly indicate lower complication rates than those reported in previous studies using conventional compression or collagen-based sealing devices [5,9,10,17]. Another advantage to this hemostatic system is that it is possible to switch to conventional compression techniques at any time during the application process to avoid major bleeding complications in case of incomplete hemostasis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…With regard to the safety of the system, the results presented in this study clearly indicate lower complication rates than those reported in previous studies using conventional compression or collagen-based sealing devices [5,9,10,17]. Another advantage to this hemostatic system is that it is possible to switch to conventional compression techniques at any time during the application process to avoid major bleeding complications in case of incomplete hemostasis.…”
Section: Discussionsupporting
confidence: 50%
“…Mechanical or manual compression techniques are not only a source of patient discomfort but represent a potential risk of puncture-site-related complications, such as bleeding, development of large hematoma, and pseudoaneurysms. This is of particular concern after employment of large sheaths and/or aggressive anticoagulation therapy [1,2,5,[17][18][19]. Furthermore, it has been proposed that applying mechanical or manual compression in patients with severe peripheral arterial occlusive disease may be critical due to considerably reduced blood flow during compression.…”
Section: Discussionmentioning
confidence: 99%
“…14-16 Several devices have been developed to aid in the closure of the femoral arteriotomy, including, extravascular plug devices (VasoSeal, AngioSeal, ExoSeal), 10,17 percutaneous suture closure devices (Perclose, StarClose), 18 and mechanical compression devices. [19][20][21][22][23] Mechanical compression devices most commonly used are the C-clamp or Compressor (Advanced Vascular Dynamics, Portland, OR) and pneumatic Femostop device (Radi Medical Systems, Uppsala, Sweden). All these devices including our AFCD provide the application of constant pressure while maintaining limb perfusion monitored by only one nurse and free up the operator.…”
Section: Discussionmentioning
confidence: 99%
“…The C-clamp and Femostop devices were compared to MC in a number of studies, [19][20][21]23 which generally reported equal efficacy with no significant differences regarding femoral vascular complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of control of bleeding after transfemoral catheterization, the mean time to hemostasis with manual compression was 33.5 minutes in a multicenter trial. 19 For the manual compression group in our study, the mean time to hemostasis was 44.7 minutes, but we found that it was necessary to use the Clo-Sur PAD in 42 patients (60%), when the time of hemostasis was Ͼ30 minutes. Therefore the actual hemostasis time in our study would have been longer if only manual compression had been used.…”
Section: Discussionmentioning
confidence: 55%